Analisis Faktor yang Mempengaruhi Enterprise Risk Management - Amir Hamzah; Yudi Febriansyah (Fakultas Ekonomi Universitas Islam 45, 2022)
This research aims to produce empirical facts / models that can explain the factors that influence ERM. To test the hypothesis that has been formulated through proving the results of the research used in statistical calculations so that the results of proof showing the rejection of Ho or acceptance of Ha are obtained. In this research, the research object was Manufacturing Companies in the Consumer Goods Industry Sector in 2019. The results of the F test show that financial leverage, company complexity and company size jointly affect ERM. The results of the t test show that financial leverage has a significant negative effect on ERM, firm size has a significant positive effect on ERM, and industry competition has no significant effect on ERM. keywords: financial leverage, industry competition, company size, ERM.